2012
DOI: 10.1007/s10741-012-9331-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease and chronic heart failure: a dangerous mix

Abstract: Chronic heart failure (CHF) is associated with a high comorbidity burden, adverse impact on quality of life and high health care utilisation. Peripheral arterial disease (PAD) and CHF share many risk, pathophysiological and prognostic features, and each has been associated with increased morbidity and mortality. PAD often goes undetected, and yet in spite of the availability of screening tools, this is not commonly considered in CHF care. A review of the electronic databases Medline, CINAHL and Cochrane CENTRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 54 publications
0
24
0
3
Order By: Relevance
“…HF patients with ischemic etiology have higher mortality 1, 2. A few studies have revealed that HF patients with peripheral artery disease had poor prognosis 28, 29. On the other hand, female is associated with a decreased mortality 1, 2…”
Section: Discussionmentioning
confidence: 99%
“…HF patients with ischemic etiology have higher mortality 1, 2. A few studies have revealed that HF patients with peripheral artery disease had poor prognosis 28, 29. On the other hand, female is associated with a decreased mortality 1, 2…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 11,304 patients with PAD, Anand et al [23] found that the prevalence of heart failure in patients with PAD was 7.9%, which was greater than the 4.1% expected from NHANES data. Thus, the prevalence of PAD is nearly doubled in the setting of heart failure, and PAD is associated with greater functional impairment and worse prognosis [23,24]. Moreover, analysis of atherosclerosis risk in community data found that low ABI values were predictive of incident heart failure events over 17 year follow-up [25].…”
Section: Discussionmentioning
confidence: 99%
“…5-7 This study adds to the current literature, and shows that PAD correlates with a more severe type of atherosclerosis even in HF. 5-7, 12 For treatment of patients with HF with PAD, appropriate comprehensive management including smoking cessation, diabetes control, and exercise training 35 following recent guidelines 5-7 is more important than usual, and may lead to improved prognosis of HF and PAD. Further investigation is needed to establish whether revascularization including peripheral percutaneous intervention 36 and surgery improves the prognosis of HF and PAD.…”
Section: Discussionmentioning
confidence: 99%